2020
DOI: 10.1007/s10531-020-01941-7
|View full text |Cite
|
Sign up to set email alerts
|

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge

Abstract: Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…The high genetic diversity recorded together with the existence of a unique population in the Adriatic Sea confers to this species a higher responsiveness to local environmental perturbations (e.g., overfishing, pollution, and mortality due to microbiological infections), as reported for invertebrate marine species [71][72][73] . Genetic interconnection due to larval dispersion between Adriatic sites represents a fundamental counterforce against local population size decline, thereby increasing the ability of population persistence 74 . Larval dispersion seems to have played a less important role due to the species' limited and patchy distribution along the Italian Tyrrhenian coast and to the separation from the Adriatic population.…”
Section: Discussionmentioning
confidence: 99%
“…The high genetic diversity recorded together with the existence of a unique population in the Adriatic Sea confers to this species a higher responsiveness to local environmental perturbations (e.g., overfishing, pollution, and mortality due to microbiological infections), as reported for invertebrate marine species [71][72][73] . Genetic interconnection due to larval dispersion between Adriatic sites represents a fundamental counterforce against local population size decline, thereby increasing the ability of population persistence 74 . Larval dispersion seems to have played a less important role due to the species' limited and patchy distribution along the Italian Tyrrhenian coast and to the separation from the Adriatic population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Florida Keys formed a single genetic cluster, 8 out of 15 pairs of sites showed significant but low genetic differentiation, with no site consistently emerging as different from the rest-a common pattern in marine systems termed 'chaotic genetic patchiness' (Johnson and Black 1982). Chaotic genetic patchiness with weak or no IBD has also been found in other sponges across the Florida reef tract (DeBiasse et al 2010;Chaves-Fonnegra et al 2015;Richards et al 2016), and in a co-occurring sponge, S. vesparium (Griffiths et al 2020), which shared many sampling sites with this study.…”
Section: Population Structure At Smaller Spatial Scalesmentioning
confidence: 94%
“…To date, empirical population genetics studies have been conducted on only four Caribbean sponge species ( Xestospongia muta : López-Legentil and Pawlik 2009 ; de Bakker et al 2016 ; Richards et al 2016 ; Callyspongia vaginalis : DeBiasse et al 2010 ; Cliona delitrix : Chaves-Fonnegra et al 2015 ; Spheciospongia vesparium : Griffiths et al 2020 ). In general, these studies have found strongly differentiated populations throughout the region, including among sites only tens of kilometres apart in some instances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic drift that occurs in this population, the existence of these alleles must be preserved. We suggest the improvement of the connectivity between zones to counterforce declining population size, low genetic diversity, and local extinction (Griffiths et al 2020) . This implies that management should be conducted not only in the zone where D. gracilis are growing but also in the surrounding area as a buffer zone.…”
Section: Implications For the Sustainable Management Of Tropical Rainmentioning
confidence: 93%